The Sharia Pension Fund Asset Management to Increase Optimal Returns: Pengelolaan Aset Dana Pensiun Syariah untuk Meningkatkan Imbal Hasil yang Optimal - Achsan, Mochammad Achsan Auza'i; Uswatun Khsasanah; Rinda Ashtuti (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
This research aims to examine the role of pension programs and the management of Islamic pension funds in ensuring a person's financial well-being during retirement. The journal provides an in-depth overview of various aspects related to pension funds, including their definition, objectives, problems, and management strategies. The review employs qualitative methodology to strengthen the understanding of the optimization of pension fund asset management. The journal focuses on investment decisions, pension fund management systems, and asset management in Islamic pension funds. It highlights optimal portfolio selection and investment strategies to maintain the balance between risk and return. The role of financial activity control and Shariah principles in pension fund management, as well as challenges in developing optimal portfolios, are discussed objectively. This journal provides insight into the importance of pension fund management in ensuring the financial well-being of participants in retirement.